Человек не отсюда - Гранин Даниил Александрович (Лениздат, 2014)
Экземпляры: ф.8 (20190716) / Инвентарный номер: 59655 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Г 77 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)6-4